Ainda a questão dos sujeitos pré-verbais em português europeu : uma resposta a Costa (2001) - Barbosa, Pilar (2006)
This article examines the arguments put forward in Costa 2001 against the idea that preverbal subjects do not A-move to Spec-IP in European Portuguese (EP). It is argued that the counter-arguments presented by Costa rely on assumptions that do not survive closer scrutiny. Even though the claim that pre-verbal subjects do not occupy the canonical position might appear counter-intuitive, it has the advantage of being part of a general theory of the Null Subject Parameter that is rather simple and yet has the ability to predict a wide range of phenomena regarding preverbal subject constructions in EP as well as in the other Romance Null Subject Languages. The standard theory might appear more intuitive, but makes none of these predictions and has trouble dealing with the same range of phenomena.